Effects of GA3 Treatments on Fruit Vascular Structure and Water Transport of Grape - Zhong-Hui Cai; Xiu-Jie Li; Charles F. Forney; Yue Wang; Bo Li; Zhao-Sen Xie (International Journal of Fruit Science)
Exogenous gibberellic acid was applied to regulate fruit growth of grapes to acquire high quality seedless berries. The vascular bundles provide the pathway of water and nutrient transport into the fruit and play an important role in berry growth and sugar accumulation. Therefore, changes in berry size and quality are closely related to the structure and function of the vascular tissue. In this study, 10-year-old “Shine Muscat” grape vines were treated with GA3 in grapevine production. Based on previous research and experimental environmental conditions, four treatments were applied: elongating cluster（5 mg L−1 GA3 on Apr. 28）+ seedless（25 mg L−1 GA3 on May. 24）+ expanding（50 mg L−1 GA3 on Jun. 7） (T1), seedless（25 mg L−1 GA3 on May. 24）+ expanding（50 mg L−1 GA3 on Jun. 7） (T2), expanding（50 mg L−1 GA3 on Jun. 7） (T3) and water (CK). Compared to CK, all fruits treated with GA3 had greater berry size. In addition, GA3 treated grapes had greater vascular bundle areas, including the areas of both phloem and xylem, as well as a greater number of vessels compared to control fruit. During the first rapid growth stage, water transport into the grape was rapid and did not differ among treatments. During veraison, the water transport rate among the four treatments differed, and the rank of speed was T2>T3>CK>T1. Therefore, we found that GA3 treatment can significantly promote the differentiation of vascular tissues and improve water transport capacity and phloem sugar unloading; T2 promoted the development of vascular bundles, enhanced water transport speed and phloem sugar unloading of fruit after veraison, and increased berry size.